Antibiotic drugs targeting bacterial RNAs - Weiling Hong; Jie Zeng; Jianping Xie (Elsevier, 2014)
RNAs have diverse structures that include bulges and internal loops able to form tertiary contacts or serve as ligand binding sites. The recent increase in structural and functional information related to RNAs has put them in the limelight as a drug target for small molecule therapy. In addition, the recognition of the marked difference between prokaryotic and eukaryotic rRNA has led to the development of antibiotics that specifically target bacterial rRNA, reduce protein translation and thereby inhibit bacterial growth. To facilitate the development of new antibiotics targeting RNA, we here review the literature concerning such antibiotics, mRNA, riboswitch and tRNA and the key methodologies used for their screening.